Longitudinal development of 5m sprint performance in young female tennis players - Kramer, T.; Valente-Dos-Santos, J.; Visscher, C.; Coelho-e-Silva, M.; Huijgen, B. C. H.; Elferink-Gemser, M. T. (Journal of Sports Sciences, 2021)
Sprint performance over short distances is a central component in young tennis players` development. This study aimed to examine the longitudinal development of sprint performance in young female tennis players, and to investigate differences between performance levels. Also potentially explanatory variables were investigated. Female tennis players aged 10-15 (N = 167) participated in a, mixed-longitudinal study (n = 48 elite; n = 119 sub-elite). Players were measured annually on the 5 m sprint as well as for possible explaining variables for 5 m sprint performance development (age, height, body mass, maturity status, lower limb explosive strength). Multilevel analysis was used to obtain a developmental model. Moreover, it was possible to predict sprint performance (5 m) based on chronological age, body size given by height, and lower limb strength performance (p < .05). Significant different developmental patterns were found for elite and sub-elite players, with elite players aged 10-14 being faster. After age 14, no significant differences were found in sprint performance between elite and sub-elite players (p > . 05). Sprint performance is an important characteristic of young female tennis players and seemed to depend on growth and maturation in parallel to physical fitness.